Improving the nutritional status of indigenous peoples optimizing the diets of the lumad children in Sitio Dulyan, Talaingod and Upper Cabaywa, Asuncion, Davao del Norte, Philippines - Ricalde, Ruby Grace J.; Alviola, Pedro A. IV (2016)
Indigenous Peoples have poorer health status compared to non-IPs due to their remote and upland location, relatively high property, and food security. Also, some of them face issues of dispossession of lands, denial of rights, and armed conflict which limit their access to stable and nutritious foods. Because of these, IP children in Talaingod, a conflict affected area was found to have very low intakes of energy and nutrients from the food that they are consuming. However, energy and nutrients intakes of the IP children in Asuncion, a non-conflict affected area are very high. Thus, there is a need to optimize their diets in order for them to have adequate amounts of energy and nutrients. This study aimed to: (i) determine the optimal diets of the IP children that meets the daily recommended energy and nutrient intakes at minimum cost, (ii) compare their current and optimized diets in terms of food composition, energy and nutrient adequacy, and cost, and (iii) compare the optimized diets of the IP children in conflict and non-conflict affected areas. Using Linear Programming, the results showed that the optimal diets are cheaper than their current diets. Also, all of the energy and nutrient requirements were met except for Carbohydrates, Fats and Calcium. This is because the foods that the children regularly consume cannot give them sufficient amounts of these nutrients. It was also found out that the diets of the IP children in conflict affected areas can give higher levels of energy and nutrients relative to non-conflict area. Thus, diversifying their diet through farming other crops especially legumes, and raising livestock should be done in order to address the nutrient deficiencies and provide additional sources of nutrients
Thesis (BS Agribusiness Economics) -- University of the Philippines Mindanao, May 2017